2014
DOI: 10.1103/physrevb.90.104509
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pairing fluctuations on the spin resonance in Fe-based superconductors

Abstract: The spin resonance observed in the inelastic neutron scattering data on Fe-based superconductors has played a prominent role in the quest for determining the symmetry of the order parameter in these compounds. Most theoretical studies of the resonance employ an RPA-type approach in the particle-hole channel and associate the resonance in the spin susceptibility χS(q, ω) at momentum Q = (π, π) with the spin-exciton of an s +− superconductor, pulled below 2∆ by residual attraction associated with the sign change… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…The appearance of the resonance implies a sign change of superconducting gap(s) between either different patches of the Fermi surface or different Fermi pockets connected by a resonance mode at momentum q (see Ref. [51] and references therein). From the modeling of our infrared absorption data, the large sharp peak in the Eliashberg function of BaFe1.9Pt0.1As2 is centered at 5.1 ± 0.6 meV (41 ± 5 cm -1 ), with a full width at half maximum of 1 meV, and is only present in the superconducting state.…”
Section: Origin Of the Bosonic Modesmentioning
confidence: 99%
“…The appearance of the resonance implies a sign change of superconducting gap(s) between either different patches of the Fermi surface or different Fermi pockets connected by a resonance mode at momentum q (see Ref. [51] and references therein). From the modeling of our infrared absorption data, the large sharp peak in the Eliashberg function of BaFe1.9Pt0.1As2 is centered at 5.1 ± 0.6 meV (41 ± 5 cm -1 ), with a full width at half maximum of 1 meV, and is only present in the superconducting state.…”
Section: Origin Of the Bosonic Modesmentioning
confidence: 99%
“…is the dynamic susceptibility of the free electrons. The RPA approximation has been used recently, for example, to estimate the effective electron interaction due to spin fluctuations 45 . This calculation is based on a perturbation expansion in powers of the bare interaction U .…”
Section: Calculation Of χS(q ω) and χC(q ω)mentioning
confidence: 99%
“…In principle, in evaluating Π s (Q, ν) one has to include also G s F s terms and combine renormalizations in the particle-hole and the particle-particle channels because in the superconducting state particles and holes are mixed [47]. Previous work on the subject [48], however, has shown that as long as all the interactions are repulsive, the effect of inclusion of these extra terms is minimal in the case of Fe pnictides and merely shifts the resonance frequency (see below) down by a few percentage points.…”
Section: A Resonance Due To the Pole In χI−nemmentioning
confidence: 99%